Morphological Characterization of an Eco Friendly Medi Grade Bio-Polymer Composites Using SEM Analysis - Queen A. Arul; Arul J. Arputham; Padmapriya Mahalingam; Dipanjan Debnath; N Kurunji Kumaran (Journal of Pharmacy and Bioallied Sciences)
Background: Medical and Dental Implant Biomaterial Research is focused on the cutting-edge interface of polymer composite material. Ongoing research and development in the bio-material field are focused on novel matrix-filler formulations of polymer composite material with improved properties in near future. Aim: This study focuses on the morphologic characterization and structural analysis of three different volume fraction of novel natural filler basalt reinforced with PEEK polymer. Materials and Methodology: The composite samples are prepared with three different volume fraction of basalt fiber in PEEK matrix, such as PBC1 having 90% PEEK and 10% basalt, PBC 2 having 80% PEEK and 20% basalt, and PBC 3 having 70% PEEK and 30% basalt. The basalt fiber influence in the composite was investigated using Scanning Electron Microscope (SEM) and X- Ray Diffraction (XRD) analysis. The crystalline structure and the grain size were examined by X-Ray diffraction method. Result: The SEM images reveal that PBC2 composite exhibits perfect bonding and less voids compared to pure PEEK, PBC1 and PBC3 composites. Conclusion: The study reports that 80% PEEK and 20% basalt fiber composite shows better structure and grain size compared to other samples with different proportions.